Class Confidence to Build a Positive Culture in Schools - Ely Tri Susiani; Miftakhu Niamah; Abdah Munfaridatus Sholihah (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Positive discipline is discipline without threats or punishment. Applying positive discipline can increase student awareness in determining the positive character of positive discipline through an agreement between the teacher and students so that students feel involved and responsible for carrying out the discipline. This study aims to determine the impact of implementing a positive culture in forming class beliefs at Bina Karya Medika Ponorogo Health Vocational School. One form of positive culture developed in schools is applying positive discipline. This type of research is Classroom action research. Classroom action research is carried out through four stages: action planning, learning actions, observation activities, and reflection to analyze the data obtained through action. The study results show that applying positive discipline and becoming a class belief will enable students to work together, collaborate, and communicate with colleagues, school principals, and other school members. Habituation of implementing religious teachings that students believe in to create a positive culture in school/class. Give an exemplary example that starts from yourself and always uses the triangle of restitution.